Development of a Spiritual Quantum Smile-Based Group Guidance Model to Improve Students’ Psychological Well-Being - Lutfiah Azzahra Ismail; Abdullah Sinring; Sahril Buchori (Jurnal IPTEK Bagi Masyarakat, 2026)
This study aimed to develop a Spiritual Quantum Smile-based group guidance model to improve students’ psychological well-being. A research and development approach was implemented through needs analysis, planning, product development, expert validation, practicality testing, revision, and limited effectiveness testing. Data were collected through questionnaires, interviews, observation, and documentation. The product was validated by material and media experts, assessed for practicality by a guidance and counseling teacher and students, and tested using a one-group pre-test and post-test design involving 10 students. The model consists of five stages: Smile Awareness, Smile Reflection, Smile Connection, Smile Spiritualization, and Smile Empowerment. Material expert validation reached 88.89%, media expert validation 74.44%, teacher practicality 90.00%, and student practicality 94.75%. The mean psychological well-being score increased from 65.50 to 102.30 (p < 0.001). The model was rated valid and practical, and post-test psychological well-being scores were higher than pre-test scores in the limited one-group trial; broader testing with a control group is required before causal effectiveness can be established.